Synthesis and antiexudative activityof pyrolin derivatives 2 - ((4-amino-5- (furan-2-yl)-1,2,4-triazol-4H-3-il)-sulfanil)-N-acetamides - N. M. Chalenko; P. A. Bezugly; A. O. Sirova; I. S. Chekman; A.M. Demchenko (The State Expert Center of the Ministry of Health of Ukraine, 2019)
The continuous research of new effective drugs is associated with a significant number of diseases, pathological conditions. Conventional treatment with existing drugs could be ineffective, or addictive, and have a large number of side effects. Therefore, the aim of modern pharmacy is to minimize the toxicity of drugs and create new modern domestic medicine that would be more effective in relation to their activity and relatively non-toxic. Derivatives of 1,2,4-triazol have considerable synthetic, pharmacological potential. That's why study of the synthetic methods of the new structures obtain, its physical, physico-chemical, biological properties may become the basic for their spector of the synthesized derivatives and biological activity widening. The aim of the work: choice on the investigation ground in silico the basic structures 1,2,4-triazol-3-thione and the special purpose synthesis of the new potential biological active compounds, definition its structure and physic-chemical properties mark of antiexudative activity. The synthesis of pyroline derivatives of 2-((4-amino-5-(furan-2-il)-1,2,4-triazol-4H-3-il)-sulfanyl)-N-acetamides was accomplished by stages. The article describes the synthesis of new pyrolin derivatives 2-((4-amino-5(furan-2-yl)-1,2,4-triazol-4H-3-il)-sulfanyl)-N-acetamide. Acetamides were obtained by alkylation of 2-((4-amino-5(furan-2-yl)-1,2,4-triazol-3-thione N-aryl-substituted α-chloroacetamides in the presence of KOH. Using Paal-Knorr condensation of the amino group at 4th position of the triazole ring modified into pyrolium fragment. Physical and chemical characteristics, chemical structure and anti-exudative activity of the obtained compounds were established. Anti-exudative activity of compounds was investigated in the experiments on the white rats in the doses 10 mg/kg comparately with reference drug-diclophenac natrium in formalin edema modulation. The paw size was measured by pletismography before drugs introduction. For the first time 24 compounds have been synthesized: 4 pyroline derivatives 2-((4-amino-5-(furan-2-il)-1,2,4-triazol-4H-3-il)-sulfanyl)-N-acetamides. In 91% of the new synthesized derivatives the antiexudative properties have been found, 5 compounds (10.9, 10.10, 10.15, 10.21, 10.1) by anti-exudative activity have exceeded the reference drug. It is considered that the investigations of these compounds by presence or absence analgesics activities are perspective.